Integration of photovoltaics and greenery in urban building envelopes: a parametric study on energy efficiency and climate resilience in tropical city - Yijun Lu; Shi An Ting; Chun Liang Tan; Stephen En Rong Tay (Energy and Buildings, 2026)

Assessing 3-D variability of ultrafine particle using a Geo-AI modelling approach: A case study in Zhunan-Miaoli, Taiwan - Chia-Wei Hsu; Yinq-Rong Chern; Jun-Jun Su; Pei-Yi Wong; Aji Kusumaning Asri; Candera Wijaya; Yu-Cheng Chen; Shih-Chun Candice Lung; Ta-Chih Hsiao; Tee-Ann Teo; Yi-Liang Shih; Chih-Da Wu (Environmental Pollution, 2025)

Multi-objective optimization of food, energy, and carbon for vertical agrivoltaic system on building façades - Yijun Lu; Chun Liang Tan; Yang He; Filip Biljecki; Stephen En Rong Tay; Siu-Kit Lau (Energy and Buildings, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

Simultaneous carbon, nitrogen and phosphorus removal in sequencing batch membrane aerated biofilm reactor with biofilm thickness control via air scouring aided by computational fluid dynamics - Chun-Hai Wei; Xin-Yu Zhai; Yu-Duo Jiang; Hong-Wei Rong; Li-Gong Zhao; Peng Liang; Xia Huang; Huu Hao Ngo (Bioresource Technology, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Distinct responses and range shifts of lizard populations across an elevational gradient under climate change - Zhong‐Wen Jiang; Liang Ma; Chun‐Rong Mi; Shi‐Ang Tao; Fengyi Guo; Wei‐Guo Du (Global Change Biology, 2023)
Ongoing climate change has profoundly affected global biodiversity, but its impacts on populations across elevations remain understudied. Using mechanistic niche models incorporating species traits, we predicted ecophysiological responses (activity times, oxygen consumption and evaporative water loss) for lizard populations at high‐elevation (

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Characterization of Neodymium Speciation in the Presence of Fulvic Acid by Ion Exchange Technique and Single Particle ICP-MS - Chun-Mei Zhao; Le-Lan Wu; Yi-Ming Wang; Ye-Tao Tang; Rong-Liang Qiu (Bulletin of Environmental Contamination and Toxicology, 2022)

Accumulation and Depuration of Cd and its Effect on the Expressions of Metallothionein and Apoptotic Genes in Litopenaeus vannamei - Ling Li; Yu-Chun Shen; Jin-Rong Liang; Hu Liu; Tian-Ci Chen; Hui Guo (Bulletin of Environmental Contamination and Toxicology, 2021)

Cathepsin V Mediates the Tazarotene-induced Gene 1-induced Reduction in Invasion in Colorectal Cancer Cells - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Chan-Yen Kuo; Rong-Yaun Shyu; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2020)

Effects of streptozotocin on pancreatic islet β-cell apoptosis and glucose metabolism in zebrafish larvae - Xue Wang; Xue-liang Yang; Ke-chun Liu; Wen-long Sheng; Qing Xia; Rong-chun Wang; Xi-qiang Chen; Yun Zhang (Fish Physiology and Biochemistry, 2020)

Ecological Risk Assessment of Neodymium and Yttrium on Rare Earth Element Mine Sites in Ganzhou, China - Chun-Mei Zhao; Xing Shi; Si-Qi Xie; Wen-Shen Liu; Er-Kai He; Ye-Tao Tang; Rong-Liang Qiu (Bulletin of Environmental Contamination and Toxicology, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

MALDI-TOF MS analysis of the extracellular polysaccharides released by the diatom Thalassiosira pseudonana under various nutrient conditions - Xin-Xin Ai; Jun-Rong Liang; Ya-Hui Gao; Samuel Chun-Lap Lo; Fred Wang-Fat Lee; Chang-Ping Chen; Chun-Shan Luo; Chao Du (Journal of Applied Phycology, 2015)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Phenotypic characterization of C57BL/6J mice carrying the Disc1 gene from the 129S6/SvEv strain - Liang-Wen Juan; Chun-Chieh Liao; Wen-Sung Lai; Chia-Yuan Chang; Ju-Chun Pei; Wan-Rong Wong; Chih-Min Liu; Hai-Gwo Hwu; Li-Jen Lee (Brain Structure and Function, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

A comparative study of bioactive secondary metabolite production in diploid and tetraploid Echinacea purpurea (L.) Moench - Chuan-gui Xu; Tie-xin Tang; Rong Chen; Chun-hui Liang; Xiang-yu Liu; Chuan-long Wu; Yue-sheng Yang; De-po Yang; Hong Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

QTL mapping for test weight by using F 2:3 population in maize - JUN-QIANG DING; JIN-LIANG MA; CHUN-RONG ZHANG; HUA-FANG DONG; ZHANG-YING XI; ZONG-LIANG XIA; JIAN-YU WU (Journal of Genetics, 2011)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Overexpression of CyclinD1 and underexpression of p16 correlate with lymph node metastases in laryngeal squamous cell carcinoma in Chinese patients - Zhi-jie Fu; Zhi-yong Ma; Qi-rong Wang; Da-peng Lei; Rong Wang; Chun-xi Liu; Xin-liang Pan (Clinical & Experimental Metastasis, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)